Report on proposed new interior design of Quiksilver Retail Shop for Quiksilver Malaysia Sdn Bhd,at Lot SF-9, Level 2, Terminal 2 Shopping Complex, 70200 Seremban, Negeri Sembilan / Ahmad Muhamad Mustaffa - Mustaffa, Ahmad Muhamad (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learned from basic technical to the final presentation of the proposed design. The project that had been chosen for the final project is to propose a New Interior Design of Quiksilver Retail Shop for Quiksilver Malaysia Sdn. Bhd at Lot SF-9, Level 2, Terminal 2 Shopping Complex, 70200 Seremban, Negeri Sembilan. This proposed retail shop is to attract users, men, women, boys and girls come and buying Quiksilver products at retail offered and at the same time to promote their product successfully as they sell everything including Roxy and DC product. The product includes clothes, pants, accessories and many more. The target market for the users of this Quiksilver product are men, women, boys and girls from all ages and classes. Concept and image that had been chosen not only must be suitable with the products, but it must have a strong impact towards the design purposes, where it will give a strong character to the shops. Connected to that, the chosen design style for Quiksilver retail shop is based on urban design, which goes all the way with the client’s needs as they want their retail to have the urban or modem beach look, and at the same time would attract the customers with to enter inside the retail. Before getting a desired design that is suitable with the client’s needs, some data analysis has been done. The research included on types of customers that usually comes to Quiksilver retail, types of services, products of the Quiksilver brand, spaces to be included in the proposed area, time operation and information about other retail that use the same system in management, as the proposed retail shop. Some of the information of the study is through interviews, printed media, internet, observation, and through the result from the case studies either locally or internationally.